(untitled) (Revista de Biblioteconomia de Brasília, 1974)
LOMBARDI, Mary. Brazilian serial documents: a selective and annotated guide. Bloomington: lndiana University Press, 1974. 445 p. (Indiana University Latin American Studies Program) ISBN 0-253-31262-0.